A Study on Mixed Convection Heat Transfer in Lid-Driven L-Shaped Cavity using COMSOL - Sudirman, Nurul Hamidah; Kamardan, Muhamad Ghazali (Enhanced Knowledge in Sciences and Technology, 2025)
This study investigates the mixed convection heat transfer in a liddriven L-shaped cavity by using COMSOL software. The dimensionless equations for mass, momentum, and energy were solved to produce streamlines and isotherms. The analysis was conducted using fixed values of Reynold number (Re), Richardson number (Ri), and Prandtl number (Pr). The results showed that forced convection is dominant in the upper part of the cavity since it is where the lid motion creates a strong recirculating flow. Meanwhile, in the lower region, it seems that there is a lack of streamlines because of the shape of the cavity and weak buoyancy. For isotherms, there is significant heat transfer at the bottom cavity shown by the closely spaced isotherm lines. The buoyancy forces generated by the heated wall caused warm air to rise, resulting in curving isotherms that show the interaction of natural and forced convection.